Soft-Etching Copper and Silver Electrodes for Significant Device Performance Improvement toward Facile, Cost-Effective, Bottom-Contacted, Organic Field-Effect Transistors - Wang, Zongrui (2017)
Poor charge injection and transport at the electrode/semiconductor contacts has been so far a severe performance hurdle for bottom-contact bottom-gate (BCBG) organic field-effect transistors (OFETs). Here, we have developed a simple, economic, and effective method to improve the carrier injection efficiency and obtained high-performance devices with low cost and widely used source/drain (S/D) electrodes (Ag/Cu). Through the simple electrode etching process, the work function of the electrodes is more aligned with the semiconductors, which reduces the energy barrier and facilitates the charge injection. Besides, the formation of the thinned electrode edge with desirable micro/nanostructures not only leads to the enlarged contact side area beneficial for the carrier injection but also is in favor of the molecular self-organization for continuous crystal growth at the contact/active channel interface, which is better for the charge injection and transport. These effects give rise to the great reduction of contact resistance and the amazing improvement of the low-cost bottom-contact configuration OFETs performance.